2020
DOI: 10.15408/ajme.v2i2.18217
|View full text |Cite
|
Sign up to set email alerts
|

Pembelajaran Dalam Jaringan Dengan Pendekatan Saintifik Berbantuan Platform Edmodo Untuk Meningkatkan Kemampuan Pemecahan Masalah Matematis Siswa Sma

Abstract: The mathematics problem-solving ability of students in Indonesia is not high yet. The students found it difficult to do the mathematics problems that lead to solving a problem. This study aims to improve students' mathematical problem-solving skills using the Edmodo platform. The study used a quasi-experimental design to find out whether the enhancement of students' mathematical problem-solving abilities that obtain using the Edmodo Platform with a scientific approach is significantly higher than the students … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
1
1
0
Order By: Relevance
“…This means that the planning, implementation, and evaluation of the learning sociology scientific approach utilizes various learning media as learning resources so that students can obtain information from various media and online in the form of WhatsApp, Google Classroom, and Google Form applications. This research is in accordance with previous research on learning the application of the scientific approach using online media, including; 1) research by Nindy Ivalyn, et al (2020) found that online learning with a scientific approach assisted by the Edmodo platform can improve mathematical problem-solving abilities and positive student responses better than only scientific approach [8]; Mega Faradilla, et al (2021) describes the planning process and implementation process using a scientific approach in online learning in social science subjects for class VII at SMP Negeri 4 Samarinda has met scientific rules [9]. Likewise, the research results of Umi Hartati, et al (2021) that the application of the Flipper Classroom learning method with a scientific approach assisted by WhatsApp in learning mathematics shows student learning outcomes in learning an average of 81.48% and it is stated that students complete the minimum completeness criteria [10].…”
Section: Teachers With Media Learning Patterns At the Evaluation Stag...supporting
confidence: 91%
“…This means that the planning, implementation, and evaluation of the learning sociology scientific approach utilizes various learning media as learning resources so that students can obtain information from various media and online in the form of WhatsApp, Google Classroom, and Google Form applications. This research is in accordance with previous research on learning the application of the scientific approach using online media, including; 1) research by Nindy Ivalyn, et al (2020) found that online learning with a scientific approach assisted by the Edmodo platform can improve mathematical problem-solving abilities and positive student responses better than only scientific approach [8]; Mega Faradilla, et al (2021) describes the planning process and implementation process using a scientific approach in online learning in social science subjects for class VII at SMP Negeri 4 Samarinda has met scientific rules [9]. Likewise, the research results of Umi Hartati, et al (2021) that the application of the Flipper Classroom learning method with a scientific approach assisted by WhatsApp in learning mathematics shows student learning outcomes in learning an average of 81.48% and it is stated that students complete the minimum completeness criteria [10].…”
Section: Teachers With Media Learning Patterns At the Evaluation Stag...supporting
confidence: 91%
“…Ideally, if the student or examinee can answer correctly for forty questions, the student or examinee will get a score of forty X 2 = 80. This number 80 is known as the Ideal Maximum Score, which is the highest score an examinee can receive if they can answer each question correctly (Ivalyn & Rahadi, 2020). This means that it is impossible for a student to score more than 80 in the learning outcome test.…”
Section: The Difference Between Scores and Gradesmentioning
confidence: 99%